Haemorrhage through the ampulla of Vater. Issue 716 (June 1985) - Ribbans, W. J.; Pounder, R. E.; Lindsay, I.
Abstract : A patient with chronic pancreatitis presented with a series of massive upper gastrointestinal haemorrhages due to bleeding into the pancreatic duct. This report emphasizes the value of intensive investigation before surgery, since it may be impossible to identify the site of bleeding at laparotomy.